Immune Checkpoint Inhibitors and Atherosclerotic Vascular Events in Cancer Patients - Inno, Alessandro; Chiampan, Andrea; Lanzoni, Laura; Verzè, Matteo; Molon, Giulio; Gori, Stefania (Frontiers in Cardiovascular Medicine, 2021)
In clinical trials and meta-analysis, atherosclerotic vascular events (AVEs) during treatment with immune-checkpoint inhibitors (ICIs) have been reported with low incidence. However, preclinical data suggest that these drugs can promote atherosclerosis inflammation and progression of atherosclerosis plaques, and there is now growing and convincing evidence from retrospective studies that ICIs increase the risk of atherosclerotic vascular events including arterial thrombosis, myocardial infarction and ischemic stroke. Prospective studies are needed to increase knowledge on long-term effect of ICIs or their combinations with other cardio-toxic drugs, but in the meantime a careful assessment and optimization of cardiovascular risk factors among patients treated with ICIs is advisable.